Assessing Students' Critical Thinking Skills in Terms of Cognitive Style: A Study of the Application of the Inquiry Collaborative Based V-Lab Model in Programming Courses - Susanti, Wilda; Nasution, Torkis; Tendra, Gusrio; Simeru, Arden; Yuliendi, Rangga Ramadian (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This study explored the assessment of students' critical thinking skills in programming courses by considering individual cognitive styles. We apply the inquiry collaborative-based V-Lab model as a learning approach, allowing students to participate in virtual experiments and interactive simulations. This approach is applied to a programming class, taking into account the student's cognitive style as the determining factor. We use measurement methods that include solution analysis, problem-solving, and critical thinking of students. The results showed that the V-Lab model based on collaborative inquiry was effective in improving students' critical thinking skills, with variations in its effect depending on the individual's cognitive style. The implications of these findings are presented for the development of more adaptive and effective learning approaches in programming courses, as well as for further research into the interaction between cognitive styles and technology-based learning.